2023
DOI: 10.1021/jasms.2c00342
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of 2-Hydroxypropyl-β-Cyclodextrin Treatment in a Neuronal-Like Cell Model of Niemann–Pick Type C Using Quantitative Proteomics

Abstract: Niemann−Pick, type C (NPC) is a fatal, neurovisceral lysosomal storage disorder with progressive neurodegeneration and no FDA-approved therapy. Significant efforts have been focused on the development of therapeutic options, and 2-hydroxypropyl-β-cyclodextrin (HP-b-CD) has emerged as a promising candidate. In cell culture, HP-b-CD ameliorates cholesterol storage in endo/lysosomes, a hallmark of the disorder. Furthermore, in animal studies, treatment with HP-b-CD delays neurodegeneration and extends lifespan. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…16 As aforementioned, RHSD was more effective than an equal dose of RES alone, indicating that HP-β-CD as an excipient can enhance the biological activity and bioavailability of resveratrol. Interestingly, preclinical and clinical data suggest that HP-β-CD can be used as an active pharmaceutical ingredient in the treatment of various neurological diseases, 65 such as inhibition of intracellular cholesterol accumulation through plasma membrane interactions, which plays a beneficial role in Niemann-Pick type C disease, 20,66 and the promising neuroprotective effect in Alzheimer's disease by cholesterol transport and Aβ clearance. 21,67 While previous research has shown the neuroprotective effects of HP-β-CD in MPTP-induced PD mouse models by increasing the autophagy, 22 further independent controlled trials are required to verify the neuroprotective effects of HP-β-CD in PD animal models.…”
Section: Discussionmentioning
confidence: 99%
“…16 As aforementioned, RHSD was more effective than an equal dose of RES alone, indicating that HP-β-CD as an excipient can enhance the biological activity and bioavailability of resveratrol. Interestingly, preclinical and clinical data suggest that HP-β-CD can be used as an active pharmaceutical ingredient in the treatment of various neurological diseases, 65 such as inhibition of intracellular cholesterol accumulation through plasma membrane interactions, which plays a beneficial role in Niemann-Pick type C disease, 20,66 and the promising neuroprotective effect in Alzheimer's disease by cholesterol transport and Aβ clearance. 21,67 While previous research has shown the neuroprotective effects of HP-β-CD in MPTP-induced PD mouse models by increasing the autophagy, 22 further independent controlled trials are required to verify the neuroprotective effects of HP-β-CD in PD animal models.…”
Section: Discussionmentioning
confidence: 99%
“…One treatment that aims to regulate cholesterol levels by improving the solubility of hydrophobic compounds is 2-hydroxypropyl-β-cyclodextrin (HPβCD). However, this drug has been observed to lower cholesterol levels in a model of neuronal NPC cells but did not normalize the levels of NPC1 and [81]. In addition, adverse events such as hearing loss, fever, and meningitis have been reported in some patients [82].…”
Section: Alterations In Endocytosis Due To Cholesterol Accumulation I...mentioning
confidence: 98%
“…What makes this compound especially important is that it acts against a range of leukemias including acute myeloid leukemia, acute lymphoblastic leukemia and chronic myeloid leukemia as well as inhibiting hypoxia-adapted cells. The compound has also been approved for treating a lysosomal lipid storage disorder, Niemann-Pick Type C disease [87].…”
Section: Medical Applicationsmentioning
confidence: 99%